Samoan medicine; Samoan patent - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A Samoan medicine against hepatitis made from the Mamala tree (Homalanthus Nutans) is currently being investigated by the Aids Research Alliance (ARA), a non profit research organisation based in the USA. The substance Prostratin is believed...